Dinamika penggunaan media buku, Audiovisual, dan ICT dalam pembelajaran PAI - Syafitri, Ruhul Zikraini; Indriany, Hafizah; Zaman, Nurul (Jurnal Pendidikan Agama Islam, 2025)
This study explores the dynamics of using book-based, audiovisual, and information and communication technology (ICT) media in Islamic Religious Education (PAI) learning. The rapid advancement of technology requires PAI teachers to adapt their teaching media to make learning more effective and engaging for students. Books remain an essential medium as a primary source of knowledge and religious values, while audiovisual media enhance understanding through contextual and interactive learning experiences. Meanwhile, ICT integration provides broader opportunities for digital learning through online platforms, educational applications, and interactive multimedia. This study employs a qualitative descriptive approach by reviewing relevant literature and field practices. The findings indicate that combining the three types of media can improve learning motivation, strengthen the comprehension of religious concepts, and foster students’ digital literacy skills. Therefore, PAI teachers should integrate these media in a balanced way to create a learning process that aligns with contemporary educational needs.